PENDEKATAN STM DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN KARAKTER PEDULI LINGKUNGAN PADA SISWAKELAS 6 SD NEGERI 1 MIRICINDE - Purwati, Puji (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
This best practice aims to convey the author's experience in using the STM approach in science learning to improve the character of environmental care in grade 6 students of SD Negeri 1 Miricinde. Strengthening character education caring for the environment in students needs to be developed from an early age, because now we are in the era of revolution 4.0. This digital era makes students increasingly indifferent to their environment. This also happened to 29 grade 6 students of SDN 1 Miricinde. Students are still wasting on the use of electrical energy, students still do not care about closing open faucets even though the tub is fully charged, advice and appeals from principals and teachers are not heeded by students. Students do not yet understand the importance of caring for the environment. The instruments used are observation sheets of students' environmental care attitudes, observation sheets of teacher activities in applying the STM approach, observation sheets of teachers' roles in instilling environmental care attitudes, and questionnaires of students' environmental care attitudes. The validity of the instrument uses expert judgment, namely the principal. Based on the overall results of observations and analysis of existing data, it can be concluded that the STM approach in science learning can improve the character of environmental care in grade 6 students of SD Negeri 1 Miricinde. Student learning outcomes have also improved. In addition to improving the character of caring for the environment, the STM approach in science learning can also increase the character of nationalism in students. The impact of implementing the STM approach for schools is that there is a decrease in electricity bills in schools.